Time-sharing of synthetic opto-genetic circuits for multiple channel access communication - Kavya Devarajan (2016)
Quantitative understanding of complex biological systems has been a major challenge. The synthetic biology toolkit helps in engineering genetic circuits to design such complex systems. To develop effective precisely-controlled circuits, rapidly regulate-able gene expression systems are necessary. Opto-genetic modules offer unprecedented ways to control cellular functions in precise spatial and temporal resolution. However, current opto-genetic systems have been limited to low dynamic expression and switchable control. Henceforth, the design of synthetic circuits for coordinated cell-cell communication has been difficult. A novel blue light-regulated genetic system is characterised in this work that demonstrates precise and stable switchable gene expression control with light intensity and pulse-width percentages. The system provides effective means of coordinated functions and thus, is applied to optically synchronize cells to perform different control functions. With such precise control, the system serves as a basis for underlying biological patterns and new developments in Systems biology and Biotechnology.